(untitled) (Research, Society and Development, 2021)
Objective: To carry out a literature review, with a systematic search, observing the evidence regarding the impact of periodontal disease on quality of life. Methodology: The research was carried out in the Medline / Pubmed, SciELO, LILACS, Web of Science and Scopus databases, in which the descriptors "Periodontal Diseases" and "Quality of Life" were used. Articles published in Portuguese, English and Spanish that portrayed the theme in the period between 2015-2020 were included. Duplicate articles and all review studies were excluded. Initially, 1435 articles were identified, leaving 36 articles after observing the eligibility criteria. Results: Periodontal disease has a negative impact on quality of life related to oral health, since, of the total articles (n = 36), thirty evidenced this statement, and the more severe the periodontal destruction, the worse the quality of life. life (n = 11). However, some studies (n = 4) have found no significant relationship between the disease and quality of life or have obtained low impact. In addition, there are results with a high impact on quality of life in the following groups: smokers, absence of health insurance, obese and diabetics, pregnant women, anxious people, elderly people, patients with terminal kidney disease, caries, high blood pressure. Conclusion: Periodontal diseases negatively affect the quality of life of affected people and there is evidence that the greater the severity of the disease, the greater its impact on quality of life. However, randomized clinical studies and longitudinal studies are needed to strengthen these findings.